Analysis Of Motivation And Job Satisfaction On Employee Performance At Hotelgrand Stabat Langkat - Damaitista, Laura; Istiqamah, Nuraini Kemalasari; Yanti, Eli Delvi (Jurnal Fokus Manajemen, 2025)
This study aims to analyze the influence of work motivation and job satisfaction on employee performance at Hotel Grand Stabat Langkat. The research method used is associative with a quantitative approach. The sample consists of 32 hotel employees selected using total sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that work motivation has a positive and significant effect on employee performance, as indicated by a t-value of 2.240 and a significance level of 0.033. Job satisfaction also has a positive and significant effect on employee performance, with a t-value of 1.745 and a significance level of 0.041. Simultaneously, both variables have a significant influence on performance with an F-value of 3.525 and a significance level of 0.043. The coefficient of determination (R²) of 0.196 indicates that 19.6% of the variation in employee performance is explained by motivation and job satisfaction, while the remaining 80.4% is influenced by other factors not examined in this study. These findings suggest that effective management of motivation and job satisfaction is essential to enhance employee performance in the hospitality industry.